Low brain iron content in idiopathic restless legs syndrome patients detected by phase imaging. Issue 13 (18th June 2013) - Rizzo, Giovanni; Manners, David; Testa, Claudia; Tonon, Caterina; Vetrugno, Roberto; Marconi, Sara; Plazzi, Giuseppe; Pizza, Fabio; Provini, Federica; Malucelli, Emil; Gramegna, Laura Ludovica; Lodi, Raffaele
ABSTRACT: Background: The objective of this study was to use phase imaging to evaluate brain iron content in patients with idiopathic restless legs syndrome (RLS). Methods: Fifteen RLS patients and 15 healthy controls were studied using gradient‐echo imaging. Phase analysis was performed on localized brain regions of interest selected on phase maps, sensitive to paramagnetic tissue. Differences between the 2 subject groups were evaluated using ANCOVA including age as a covariate. Results: Significantly higher phase values were present in the RLS patients compared with healthy controls at the level of the substantia nigra, thalamus, putamen, and pallidum, indicating reduced iron content in several regions of the brain of the patients. Conclusions: We have used MRI phase analysis to study brain iron content in idiopathic RLS in vivo for the first time. Our results support the hypothesis of reduced brain iron content in RLS patients, which may have an important role in the pathophysiology of the disorder. © 2013 International Parkinson and Movement Disorder Society